Branding Strategy for the Band “The Flins Tone” through a Showcase Titled “The Flins Tone 19 Years Still Pop Punk Showcase” - Syafira Azzahra (Repertoar, 2026)
This study aims to analyze the branding strategies implemented by the band The Flins Stone through the “The Flins Stone 19 Years Still Pop Punk Showcase” event and to examine their impact on the band’s continued existence. The study employs a descriptive qualitative approach using interviews, observation, documentation, and questionnaires. The results show that the branding strategy was realized through clear market segmentation, differentiation of the pop-punk identity, the personification of each band member, and a showcase experience that featured music, visuals, interaction, and gimmicks. These strategies proved effective in strengthening the band’s image, maintaining the loyalty of long-time fans, and attracting new audiences. Thus, the showcase served not only as a celebration of the band’s 19-year career but also as an effective way to expand the reach of the Indonesian pop-punk market.